2010
DOI: 10.1111/j.1574-6941.2010.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of resource limitation of bacteria along a trophic gradient in Mediterranean inland waters

Abstract: The nature of the resource that limits heterotrophic bacteria, i.e. mineral nutrients or carbon (C), has consequences for biogeochemical cycles in aquatic ecosystems. Our aim was to identify the resource [C or phosphorus (P)] that mainly limits bacteria in a set of 31 Mediterranean inland water ecosystems spanning a wide trophic range. We followed an intersystem observational approach with three complementary perspectives, comparing the bacterial demand with the resource supply in terms of both the quantity (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 51 publications
3
20
2
Order By: Relevance
“…Nevertheless, and in agreement with our hypothesis, photorepair mechanisms were insufficient to completely counteract UVR-induced damage, this being concordant with a sharp decrease in the UV-A : UV-B ratio (58 %) in the upper layers (subsurface conditions). Moreover, the increased HBP found after exposure of samples to higher PAR intensity in the upper layers is consistent with the previously reported stimulatory effect of PAR on HBP (Morán et al, 2001;Medina-Sánchez et al, 2002;Pakulski et al, 2007). Furthermore, a potential presence of aerobic anoxygenic phototrophic bacteria (Bertoni et al, 2011;Mašín et al, 2012;Ferrara et al, 2011) should not be ruled out in accounting for the increased HBP under high PAR in the low-UVR lake.…”
Section: Sensitivity Of Phytoplankton and Bacteria To Uvr And Stratifsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, and in agreement with our hypothesis, photorepair mechanisms were insufficient to completely counteract UVR-induced damage, this being concordant with a sharp decrease in the UV-A : UV-B ratio (58 %) in the upper layers (subsurface conditions). Moreover, the increased HBP found after exposure of samples to higher PAR intensity in the upper layers is consistent with the previously reported stimulatory effect of PAR on HBP (Morán et al, 2001;Medina-Sánchez et al, 2002;Pakulski et al, 2007). Furthermore, a potential presence of aerobic anoxygenic phototrophic bacteria (Bertoni et al, 2011;Mašín et al, 2012;Ferrara et al, 2011) should not be ruled out in accounting for the increased HBP under high PAR in the low-UVR lake.…”
Section: Sensitivity Of Phytoplankton and Bacteria To Uvr And Stratifsupporting
confidence: 92%
“…In this regard, it has been widely reported that greater exposure to UVR exerts an inhibitory effect on autotrophic and heterotrophic organisms (Häder et al, 2011), and that UV-B (280-315 nm), in particular, harms primary and bacterial production , enzymatic activity (Korbee et al, 2012), and cell viability , among other effects. However, it has been also reported Medina-Sánchez et al, 2002;) that UVR does not produce negative effects and it can even stimulate bacterial production and photosynthetic activity. These opposite effects may be attributable to the high acclimation capacity of organisms in high-UVR ecosystems Ruiz-González et al, 2013) or to differences in physical-chemical factors (e.g., temperature or nutrient content) among ecosystems (Harrison and Smith, 2009).…”
Section: P Carrillo Et Al: Synergistic Effects Of Uvr and Simulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…farming and cattle raising). Moreover, those ecosystems tend to be more autotrophic with greater eutrophy, as has been reported based on estimated BR:PP ratio values [32], probably related to the restricted terrestrial C input [36]. Likewise, the Mediterranean freshwater ecosystems undergo intense and irregular Saharan dust loads that constitute notable inputs of P [37][39] and of soil-derived organic components to these water bodies [39], [40].…”
Section: Introductionmentioning
confidence: 59%
“…Thus, studies performed in freshwater ecosystems involve arctic and alpine lakes [20], [29], tropical regions [26], [30], [31] or humic lakes [13], whereas inland waters of Mediterranean region have received less attention. Noticeably, the Mediterranean ecoregion shows a broad intersystem trophic gradient for inland waters, not only throughout the entire ecoregion, but also locally [32]. This has been promoted by traits such as scarceness of vegetation and developed soil on watersheds [33], the high frequency of extreme weather events [34], [35], and millennia of land use (i.e.…”
Section: Introductionmentioning
confidence: 99%